2018
DOI: 10.3390/e20060412
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation on Nanofluid Thin Film Flow of Eyring–Powell Fluid with Thermal Radiation and MHD Effect on an Unsteady Porous Stretching Sheet

Abstract: This research paper investigates entropy generation analysis on two-dimensional nanofluid film flow of Eyring-Powell fluid with heat amd mass transmission over an unsteady porous stretching sheet in the existence of uniform magnetic field (MHD). The flow of liquid films are taken under the impact of thermal radiation. The basic time dependent equations of heat transfer, momentum and mass transfer are modeled and converted to a system of differential equations by employing appropriate similarity transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…Daniel et al 48 tackled down the issue of thermal disorderness in time non-reliant heating motion of a current passing tiny particles dispersion and heating transportation in a pores keeping linear expanding material accompanying the collective projections of electricity and MHD reliant fields, solar rays emission, viscousness loss, and species combination using implicit finite difference method in which the joint heating phenomena and parameters like buoyancy have reverse effects on Bejan number. Ishaq et al 49 worked on irreversibility in two directional tiny particle dispersion movement of Powell Eyring suspension accompanying heating and saturation transmitting on an expanding material keeping pores prevailing the similar magnitude of external agent proving that thermal disorderness kept incremental position on incrementing dissipative representative, Hartmann and other numbers. Daniel et al 50 presented the irreversibility phenomena and its reciprocal in time non-reliant heating motion of current passing hydromagnetic tiny particles dispersion with suction/injection at the wall using feasible and realistic applicable tiny particles dispersion formulation for assisting informations.…”
mentioning
confidence: 99%
“…Daniel et al 48 tackled down the issue of thermal disorderness in time non-reliant heating motion of a current passing tiny particles dispersion and heating transportation in a pores keeping linear expanding material accompanying the collective projections of electricity and MHD reliant fields, solar rays emission, viscousness loss, and species combination using implicit finite difference method in which the joint heating phenomena and parameters like buoyancy have reverse effects on Bejan number. Ishaq et al 49 worked on irreversibility in two directional tiny particle dispersion movement of Powell Eyring suspension accompanying heating and saturation transmitting on an expanding material keeping pores prevailing the similar magnitude of external agent proving that thermal disorderness kept incremental position on incrementing dissipative representative, Hartmann and other numbers. Daniel et al 50 presented the irreversibility phenomena and its reciprocal in time non-reliant heating motion of current passing hydromagnetic tiny particles dispersion with suction/injection at the wall using feasible and realistic applicable tiny particles dispersion formulation for assisting informations.…”
mentioning
confidence: 99%
“…The governing equations are transformed into Ordinary equations. The nonlinear problems (8)(9)(10)(11)(12) and (15) subject to the given boundary conditions formulate two-point BVPs. The system is solved through numerical shooting technique, transforming the BVPs into initial value problems (IVPs) first.…”
Section: Discussionmentioning
confidence: 99%
“…Rasool et al [6,7] reported on some interesting findings in Marangoni convection of nanofluids involving simple as well as Riga plates with various other important physical parameters, respectively. Some recent and interesting articles can be found in [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and cross references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [9] studied the nanofluid film flow of Eyring-Powell with graphene nanoparticles. The recent study of nanofluid flow of non-Newtonian fluids using different models in different geometries can be seen in [10][11][12]. Jawad et al [13,14] investigated magneto hydrodynamic nanofluid thin film flow with the joule and slip effect.…”
Section: Introductionmentioning
confidence: 99%